Manajemen Penggunaan Teknologi Informasi Perkantoran di Sekolah - Darmansah, T.; Aulia, Ainun Meryna; Syifa, Salsabila Mayla Nadhira; Ardilla, Ovi; Safitri, Ika (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This study aims to evaluate the effectiveness of information technology usage in office activities within schools. Using a qualitative approach, data were collected from in-depth interviews with administrative staff and teachers at several schools in Jakarta. The results indicate that the use of information technology can enhance efficiency and accuracy in administrative processes, reduce manual workload, and expedite decision-making. However, challenges exist in terms of training and technology adaptation for some staff members. This study recommends continuous training and improvement of technological infrastructure to maximize the benefits of information technology in school environments.